ANALYSIS OF THE USE OF RUBBER FROM TIRE TREADING ON CONCRETE PAVERS - de Bastiani, Gustavo Vicensi; Cecconello, Vinício; Schäfer , Maurício (ARACÊ, 2024)
Reusing tire rubber in concrete pavers is an environmentally sustainable alternative, reducing the exploitation of natural resources and contributing to solid waste management. Therefore, the research analyzed the replacement of natural aggregates with rubber waste from tire retreading. The replacement of fine aggregate with rubber occurred at percentages of 5%, 10%, and 15%, in which 160 pavers of each mix were produced. The moisture content of the concrete in the fresh state was analyzed to analyze the behavior of these modifications. In the hardened state, the pavers were subjected to compression resistance, abrasion resistance, impact resistance, total water absorption, specific mass and void index tests. The use of rubber waste proved a reduction of 47.39%, 51.83%, and 77.79% for composite pavers with 5%, 10%, and 15%, respectively, with the reference mix. Furthermore, positive and satisfactory results were obtained for abrasion and impact resistance tests.